Fotocatálise heterogênea associada à adsorção em cerâmica modificada para remoção de ciprofloxacino - Brito, Cristiano Régis Freitas de (2013)
This work presents a study of the physical-chemical removal of ciprofloxacin, an antibiotic used worldwide, from a synthetic effluent, through processes of heterogeneous photocatalysis and adsorption in ceramics modified with titanium dioxide. First of all, it was tested glass and aluminum pallets and ceramics spheres as TiO2 (photocatalyst) support and carried out runs in semi continuous reactor to evaluate the compound removal. The ceramics were found to be the best substrate for TiO2 due to its adsorptive and mechanical properties, making it necessary to study adsorption characteristics as well as computational simulations to evaluate the combined process. The following process variables were studied: initial concentration, inlet flow, UV radiation potency and sintering temperature of the ceramic. It was found that the average ciprofloxacin removal by glass, aluminum and ceramic were, respectively, 70.7%, 57.4% and 93.5%, and heterogeneous photocatalysis process followed a first order kinetic in all of them. In the study of adsorption properties of the ceramics, it was found that the data best fitted to the model of pseudo first order kinetic for both sintering temperatures (550ºC and 700ºC). Among the evaluated conditions, the ones which resulted in higher removals were: inlet flow of 17.5 L.h-1-, initial concentration of 25 mg.L-1 (low concentration), using 4 UV lamps (potency of 36 W) and sintering temperature of 550ºC. In the adsorption process, the results showed that the intra particle diffusion was the limiting step in the adsorption of ciprofloxacin in the ceramics sintered at 550ºC, but it is not for the ceramic sintered at 700ºC. In the evaluation of the combined process (photocatalysis and adsorption) the results indicated that the adsorption showed a significant decrease in the removal efficiency for consecutive runs, due probably to the saturation of the active sites. However, photocatalysis process acts degrading the adsorbed ciprofloxacin, maintaining the removal efficiencies almost constants. The computational simulations estimated that the photocatalysis itself provided around 30.5% and 23% removal (from the total concentration), for the Ceramics 550 and Ceramics 700, respectively.